2020
DOI: 10.3390/polym12081696
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Investigation on the Wetting Behavior and Interfacial Joining of Polymer-Metal Interface

Abstract: Polymer-metal hybrid structures can reduce the weight of components while ensuring the structural strength, which in turn save cost and subsequently fuel consumption. The interface strength of polymer-metal hybrid structure is mainly determined by the synergistic effects of interfacial interaction and mechanical interlocking. In this study, the wetting behavior of polypropylene (PP) melt on metal surface was studied by molecular dynamics simulation. Atomistic models with smooth surface and nano-column arrays o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Thus, molecular dynamics (MD) as an advantageous tool for studying the interface of metals and polymers has been of particular interest. Zhou et al , investigated the wetting behavior of polymers and the effects of different surface structures of aluminum on interfacial interaction by using the MD method, whereas which type of interaction is not specifically mentioned. As for the polyphenylene sulfide (PPS)–copper interface obtained by nanoinjection, MD simulation conducted by Li et al showed that nanopits with slope or rounded boundaries were beneficial to interactive behavior and bonding performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, molecular dynamics (MD) as an advantageous tool for studying the interface of metals and polymers has been of particular interest. Zhou et al , investigated the wetting behavior of polymers and the effects of different surface structures of aluminum on interfacial interaction by using the MD method, whereas which type of interaction is not specifically mentioned. As for the polyphenylene sulfide (PPS)–copper interface obtained by nanoinjection, MD simulation conducted by Li et al showed that nanopits with slope or rounded boundaries were beneficial to interactive behavior and bonding performance.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that as the thermal conductivity of the substrate increases, leading to a higher cooling rate, the temperature of the melt decreases, resulting in larger contact angles and increased sphericity. In addition, Zhou et al [ 21 ] found that increasing an aluminum substrate’s temperature enhances the interaction between a polypropylene droplet and the substrate, resulting in an increased contact area between the PP droplet and the substrate, subsequently leading to a smaller contact angle. Materials with high thermal conductivity (K) can effectively transfer and dissipate heat [ 27 ], leading to faster cooling and the maintenance of spherical microparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we discovered that the interaction between the jetted-molten droplet and surface influences the resulting particle shape (sphericity). The substrate’s roughness, surface energy, along with the surface tension of the melt have been found to be crucial factors affecting the shape of the solidified particle [ 16 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Molecular dynamics (MD) simulations have attracted a lot of attention in nanoscale analysis. MD simulations [10,11] are a method suitable for atomic-scale calculations and have been widely applied to the investigation of hetero interfacial interactions and adhesion mechanisms between interfaces. This method can be adopted to observe the atomic motion of the interaction, providing a view of the dynamic evolution.…”
Section: Introductionmentioning
confidence: 99%